Physical exercise habits are related with reduced prevalence of falling among elderly women in China - Cuiqing Zhao; Tongling Wang; Dawei Yu; Wang Li (BMC, 2023)
Abstract Background Although some studies have examined the association between exercise and falls, most have focused on specific exercises, and the results have been inconsistent. In addition, there is a lack of evidence on elderly Chinese women who have different living and exercise habits compared to those in other countries. Therefore, this study aimed to investigate whether physical exercise is associated with falls in elderly Chinese women. Methods This cross-sectional study included 1429 elderly Chinese women with a mean age of 69.2 years. Information on physical exercise habits and fall experiences was collected using a self-report questionnaire. Logistic regression models were used to analyze the association between physical exercise habits and falls. Results The results showed that 15% participants had a fall in the past year. After adjusting for confounding factors, the odd ratios (ORs) and 95% Confidence Intervals (CIs) for fall experiences across categories of exercise frequency were as follow: 1 (reference) for no exercise behavior, 0.50 (0.29, 0.85) for exercise 1 to 5 times a week, and 0.37 (0.25, 0.55) for exercise more than 6 times a week. Furthermore, the ORs (95% CIs) across categories of exercise insistence were 1 (reference) for less than 1 year, 0.78 (0.37, 1.65) for 1 to 3 years, and 0.38 (0.20, 0.74) for more than 3 years. In terms of exercise duration, the ORs (95% CIs) for < 1 h/day, 1-2 h/day, and > 2 h/day were 1 (reference), 0.85 (0.53, 1.36), and 2.80 (1.30, 6.05). Unlike other variables, longer exercise duration was associated unfavorably with falls. Conclusion Physical exercise habits were associated with falls in elderly Chinese women. Keeping a proper exercise habit may contribute to lower risk of falling in elderly women.